Modifications in fire frequency impact belowground plant components in old‐growth grasslands, posing risks to their resilience - Bombo, Aline Bertolosi [UNESP]; Fidelis, Alessandra [UNESP]; Le Stradic, Soizig (Wiley, 2025)
PREMISE: In edaphic old-growth grasslands, the low nutrient content of the soil restricts plant species establishment. Additionally, fire remains an important factor in shaping vegetation structure and belowground biomass investment in old-growth grasslands, such as the campos rupestres. However, how fire frequency affects the belowground components of these grasslands remain poorly understood. Addressing this gap is essential for understanding plant resilience and regeneration strategies in fire-prone ecosystems worldwide and advancing trait-based perspectives on plant persistence under recurrent disturbances. METHODS: We compared plant belowground components across three campos rupestres sites differing in fire frequencies (1, 6, and 10 fires in 34 years). At each site, we quantified fine root biomass, specialized belowground organ biomass, bud bank size, bud-bearing organ density, and organ composition to evaluate how repeated fires shape belowground traits related to persistence and regeneration. RESULTS: High fire frequencies reduced bud bank size and belowground organ density, but altered organ composition: Graminoid and forb rhizomes declined in number, whereas woody rhizomes became more common. Overall, belowground organ biomass increased with increasing fire frequency, but fine root biomass decreased. CONCLUSIONS: Our study indicates that changes in belowground components driven by fire frequency may lead to irreversible shifts in community structure, where very frequent fires can jeopardize the resilience of the campos rupestres. For such systems, novel fire regimes can have devastating effects, threatening biodiversity, compromising conservation status, and reducing ecosystem services.